ABO BLOOD GROUP SYSTEM: IN THE CONTEXT OF HUMAN DISEASES - Obi SO; Bukar A; Digban KA; Hamza A; Waziri G; Medugu JT; Osakue EO; Olaniyan Mf; Jeremiah ZA (Ntec Specialist, 2018)
Background: The expression of ABO blood group antigens on red cell surface and a variety of human cells, tissues and fluids is well documented. Studies in the recent times have reported association between these blood group antigens and some disorders in man. Cancer, Cardiovascular disease and infection are some of the disorders reported. The interplay has given rise to the assertion that ABO blood group system has extended its clinical significance beyond the natural frontier of transfusion Science. This narrative review aims at summarizing information concerning the role of these blood antigens in the pathogenesis of human disorders such as cardiovascular, cancer and infectious diseases. Methodology: Literature on the role of ABO blood group antigens in human disease was searched from BMCMed, PubMed and text books. The search words were ABO blood group antigens, cardiovascular disease, von Willebrand factor, cancer, infectious disease, and neuroscience. We reviewed, evaluated and summarized the relationship between these disorders and ABO blood group; and possible pathogenic mechanism involved. Conclusion: It is now known that non - O blood group antigens are linked with the risk for cardiovascular disease, oncological states and infectious disorders. However further studies are needed to elucidated molecular mechanism/s in the interplay between these antigens and human health. This may as well elevate ABO blood typing as a veritable tool for cardiovascular and oncologic disorders risk assessment.